PENDAMPINGAN EKS PEKERJA MIGRAN INDONESIA DALAM PEMBUATAN AKUN MARKET PLACE ( SHOPEE) - Sururi, Sururi; Fanani, Ikhsan; Bahagia Rizka, Royke; Hermawan, Wawan; Rizal, Rahyang; Juhriah Lukitawati, Lia (Jurnal Pengabdian Kepada Masyarakat, 2024)
Indonesian Migrant Workers (PMI) who have returned to their homeland have great potential to develop businesses through digital platforms. The mentoring program for creating Shopee marketplace accounts is one solution to help ex-IMW market their products online. This study aims to analyze the mentoring process for ex-IMW in creating Shopee accounts and identify effective challenges and strategies in the process. The method used is a qualitative approach with data collection techniques through participatory observation, in-depth interviews, and documentation of 15 ex-IMW who participated in the mentoring program. The results showed that through intensive mentoring, participants successfully created Shopee accounts and understood the basic features of the platform. The main challenges faced include digital literacy constraints, limited understanding of product photography, and inventory management. Effective strategies include a gradual learning approach, one-on-one mentoring, and direct practice in managing online stores. This study recommends the need for sustainable mentoring programs and collaboration with various stakeholders to support the success of ex-IMW in developing businesses through digital platforms